A method for preparing a high-capacity and high-rate negative electrode sheet, a negative electrode sheet and a battery

By using a silane coupling agent to perform a condensation reaction with hard carbon materials and performing heat treatment at high temperatures, an inorganic material solidified negative electrode sheet is generated, which solves the performance deficiencies of the existing negative electrode sheets and achieves higher capacity, efficiency and stability. sex.

CN118825203BActive Publication Date: 2025-01-21SODIUM TECHNOLOGY CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411296698.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-21
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing negative electrode sheets have poor performance in circulation performance, rate performance, peel strength, swelling performance, etc., and the bonding strength between the binder and hard carbon material is insufficient.

Method used

A silane coupling agent is used as the negative electrode binder, and Si-OH bonds are generated through a double condensation reaction in an acidic solution, which undergoes a dehydration condensation reaction with hydroxyl, carboxyl and other groups on the surface of the hard carbon material to stabilize the bond between the hard carbon particles. Through interaction and heat treatment at high temperatures, the silane coupling agent is decomposed to generate inorganic materials and solidifies the particles in the anode system.

Benefits of technology

Significantly improve the gram capacity, first charge efficiency, peel strength, swelling performance, charge rate and cycle performance of the negative electrode sheet, and reduce the internal resistance (DCR) of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825203B_ABST
    Figure CN118825203B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing a high-capacity and high-rate negative electrode sheet, comprising: dissolving a silane coupling agent into an acidic solution to undergo a dicondensation reaction to obtain a mixed solution, wherein the silane coupling agent satisfies the chemical formula Y-R-Si(OR)3, Y represents an organic functional group, R represents an alkyl group, and the pH value of the acidic solution is 3-6, at least a hard carbon material is uniformly mixed into the mixed solution to obtain a slurry, the slurry is applied to a current collector, and a pole roll is obtained by drying, and the pole roll is heat-treated under an inert atmosphere, the heat treatment temperature is 500-900°C, and the heat treatment time is 1-2 hours to obtain a negative electrode sheet. The present application also provides a negative electrode sheet and a battery. The present application selects a silane coupling agent as a binder, and then performs a high-temperature treatment to cause the silane coupling agent to crack to form an inorganic material to solidify all particles in the negative electrode system, thereby improving the gram capacity, first charge efficiency, peel strength, swelling performance, charge rate and cycle performance of the negative electrode sheet, thereby helping to reduce the internal resistance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a method for preparing a high-capacity and high-rate negative electrode sheet, a negative electrode sheet and a battery. Background Art

[0002] At present, the negative electrode sheets prepared by hard carbon materials usually use at least one of styrene-butadiene rubber and carboxymethyl cellulose as a binder. The binding force between such binders and hard carbon materials is weak, which affects the cycle performance, rate performance, peel strength and swelling performance of the electrode sheets. Summary of the invention

[0003] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a high-capacity and high-rate negative electrode sheet, thereby improving the gram capacity, first charge efficiency, peel strength, swelling performance, charge rate and cycle performance of the negative electrode sheet.

[0004] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing a high-capacity and high-rate negative electrode sheet, comprising:

[0006] Dissolving a silane coupling agent in an acidic solution to undergo a dicondensation reaction to obtain a mixed solution, wherein the silane coupling agent satisfies a chemical formula of YR-Si(OR)3, Y represents an organic functional group, R represents an alkyl group, the pH value of the acidic solution is 3-6, the concentration of the silane coupling agent in the mixed solution is 1 wt %-5 wt %, and the reaction time for obtaining the mixed solution is 30-60 min;

[0007] At least uniformly mixing the hard carbon material into the mixed solution to obtain a slurry, wherein the mass ratio of the hard carbon material to the silane coupling agent is 80-97:2-15;

[0008] Applying the slurry to a current collector and drying it to obtain a pole coil;

[0009] The electrode coil is heat-treated under an inert atmosphere at a temperature of 500-900° C. for 1-2 hours to obtain a negative electrode sheet.

[0010] In some possible implementations, the preparation of the slurry further comprises:

[0011] filtering the mixed solution in which the hard carbon material is added to obtain a first mixture, and washing the first mixture with deionized water until it becomes neutral;

[0012] adding a conductive agent to the first mixture after cleaning to obtain a second mixture;

[0013] Add water to the second mixture and mix well to obtain the slurry.

[0014] In some possible implementations, the mass ratio of the hard carbon material, the silane coupling agent and the conductive agent is 80-97:2-15:1-5.

[0015] In some possible implementations, the viscosity of the slurry is 3000-6000 mPa•s.

[0016] In some possible implementations, when heat treating the pole coil, a metal clip is used to fix the pole coil.

[0017] The present application also provides a negative electrode sheet obtained by the preparation method as described above.

[0018] The present application also provides a battery, comprising a positive electrode sheet, an electrolyte and the negative electrode sheet, wherein the electrolyte is at least disposed between the positive electrode sheet and the negative electrode sheet.

[0019] In some possible implementations, the battery further includes a separator, wherein the separator is spaced between the positive electrode sheet and the negative electrode sheet, and the electrolyte is a liquid electrolyte.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In the present application, a silane coupling agent is used as a negative electrode binder. During the production of the electrode sheet, the Si-OH bond generated by the silane condensation reacts with the hydroxyl group, carboxyl group and other groups on the surface of the hard carbon material to undergo a dehydration condensation reaction, thereby stabilizing the interaction between the hard carbon particles. In addition, on this basis, the dried electrode sheet is subjected to high temperature treatment, and the silane coupling agent is further cracked to generate inorganic materials in situ, and all particles in the negative electrode system are solidified to form an integrated negative electrode sheet, thereby improving the gram capacity, first charge efficiency, peel strength, swelling performance, charge rate and cycle performance of the negative electrode sheet. In addition, the battery including the above-mentioned negative electrode sheet is also conducive to reducing the internal resistance (DCR).

[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of a method for preparing a high-capacity and high-rate negative electrode sheet provided in one embodiment of the present application;

[0024] Figure 2 This is a schematic diagram of the reaction of the silane coupling agent undergoing dicondensation;

[0025] Figure 3 Schematic diagram of the condensation reaction between hard carbon material and silane coupling agent;

[0026] Figure 4This is a diagram of the bonding mechanism of the negative electrode sheet obtained after high-temperature treatment. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0029] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0030] Reference Figure 1 , an embodiment of the present application provides a method for preparing a high-capacity and high-rate negative electrode sheet, comprising:

[0031] Step S101: dissolving a silane coupling agent in an acidic solution to undergo a dicondensation reaction to obtain a mixed solution, wherein the silane coupling agent satisfies the chemical formula YR-Si(OR)3, where Y represents an organic functional group and R represents an alkyl group, and the pH value of the acidic solution is 3-6. The silane coupling agent is hydrolyzed under acidic conditions to generate corresponding silane triols, and then two molecules of triols undergo a condensation reaction to generate corresponding dicondensates. The condensation reaction route of the hydrolyzed silane coupling agent is as follows: Figure 2 As shown, two free hydroxyl groups remain after the condensation of silicon triol. Exemplarily, Y can be one of vinyl, amino, epoxy, methacryloxy, mercapto or urea. Specifically, exemplary, the silane coupling agent can include at least one of γ-aminopropyltriethoxysilane or 3-methylpropyltrimethoxysilane.

[0032] Exemplarily, the acidic solution may be selected from one of ethanol aqueous solution, propanol aqueous solution, dilute HCl (mass concentration of 1%) or dilute HNO 3 (mass concentration of 1%).

[0033] In the mixed solution, the concentration of the silane coupling agent is 1 wt %-5wt %, and the reaction time to obtain the mixed solution is 30-60 min. The combination of the above concentration and reaction time is conducive to ensuring the condensation effect of the silane coupling agent after hydrolysis, preventing the excessive condensation from causing too few hydroxyl residues or incomplete condensation from causing monomer residues, thereby affecting the subsequent reaction of the silane coupling agent.

[0034] Step S102: at least uniformly mix the hard carbon material into the mixed liquid to obtain a slurry. For example, the hard carbon material and the mixed liquid can be uniformly mixed by stirring. The mass ratio of the hard carbon material to the silane coupling agent is 80-97:2-15.

[0035] Exemplarily, the hard carbon material may be selected from at least one of biomass, minerals, or resins.

[0036] Reference Figure 3 In this step, the hydroxyl or carboxyl groups on the hard carbon material will undergo a dehydration condensation reaction with the hydroxyl groups remaining on the condensed silanol.

[0037] In some embodiments, the preparation of the slurry further comprises:

[0038] The mixed solution to which the hard carbon material is added is filtered to obtain a first mixture, and the first mixture is washed with deionized water until it becomes neutral.

[0039] A conductive agent is added to the first mixture after washing to obtain a second mixture. Exemplarily, the conductive agent can be selected from at least one of carbon black (such as Super-P, KS-6), VGCF (carbon nanofiber conductive agent), multi-walled CNT (multi-walled carbon nanotube) or single-walled CNT (single-walled carbon nanotube).

[0040] Water is added to the second mixture, and the mixture is mixed uniformly to obtain the slurry. Exemplarily, the mixing can be achieved by stirring.

[0041] In some embodiments, the viscosity of the slurry is 3000-6000 mPa•s. Controlling the viscosity facilitates controlling the coating thickness and coating uniformity, thereby further improving the peel strength of the negative electrode sheet.

[0042] In some embodiments, the mass ratio of the hard carbon material, the silane coupling agent and the conductive agent is 80-97:2-15:1-5. The appropriate proportion of the silane coupling agent in the system is controlled to prevent the silane coupling agent from decomposing and producing too much gas during high-temperature treatment, thereby reducing the holes in the negative electrode sheet, and further improving the peel strength of the negative electrode sheet. The conductive agent is added to the system to form a conductive network in the hard carbon material particles and inorganic particles when the negative electrode sheet is obtained, thereby improving the conductivity of the electrode sheet. In addition, the conductive agent is generally nano-scale, and too much conductive agent is prone to agglomeration, thereby affecting the poor uniformity of the electrode sheet. In addition, the specific surface area of ​​nano-scale materials is relatively high, and too much conductive agent will cause too many interfaces, thereby affecting the conductive properties of the electrode sheet. Therefore, the proportion of the conductive agent is controlled to improve the uniformity and conductive properties of the system of the present application.

[0043] Step S103: Apply the slurry to a current collector and dry to obtain a pole coil. For example, the current collector may be a metal foil, such as a copper foil or an aluminum foil.

[0044] Step S104: heat-treating the electrode coil under an inert atmosphere at a temperature of 500-900°C for 1-2 hours to obtain a negative electrode sheet. For example, nitrogen or argon can be used to form an inert atmosphere. In the heat treatment step, the condensed silane coupling agent is cracked to generate inorganic particles in situ, thereby solidifying all particles in the negative electrode system to form an integrated negative electrode sheet. For details, refer to Figure 4 , Figure 3 In the figure, 11 is a current collector, 12 is hard carbon particles, and 13 is inorganic particles formed by cracking the silane coupling agent. The inorganic particles formed by cracking and solidifying the hard carbon particles can strengthen the binding force between the binder and the hard carbon material.

[0045] In some embodiments, when the pole coil is heat treated, a metal clamp is used to fix the pole coil, thereby preventing the pole coil from curling during the heat treatment process. Furthermore, fixing with the metal clamp can avoid the problem of subsequent flattening, and a negative electrode sheet that can be directly used can be obtained. Exemplarily, the clamping pressure provided by the metal clamp is at least 800 MPa.

[0046] Another embodiment of the present application provides a negative electrode sheet, which is obtained by the above-mentioned preparation method.

[0047] Another embodiment of the present application further provides a battery, the battery comprising a positive electrode sheet, an electrolyte and a negative electrode sheet obtained in the above embodiment, wherein the electrolyte is at least disposed between the positive electrode sheet and the negative electrode sheet. Exemplarily, the electrolyte may be a liquid electrolyte or a solid electrolyte. Exemplarily, the electrolyte may be an electrolyte conventionally used in batteries, and its specific composition is not repeated here.

[0048] Exemplarily, the battery may be a sodium ion battery or a lithium ion battery.

[0049] In some embodiments, the battery further comprises a separator, the separator is spaced between the positive electrode sheet and the negative electrode sheet, and the electrolyte is a liquid electrolyte. Exemplarily, the material of the separator can be one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.

[0050] In the present application, a silane coupling agent is used as a negative electrode binder. During the production of the electrode sheet, the Si-OH bond generated by the silane condensation reacts with the hydroxyl group, carboxyl group and other groups on the surface of the hard carbon material to undergo a dehydration condensation reaction, thereby stabilizing the interaction between the hard carbon particles. In addition, on this basis, the dried electrode sheet is subjected to high temperature treatment, and the silane coupling agent is further cracked to generate inorganic materials in situ, and all particles in the negative electrode system are solidified to form an integrated negative electrode sheet, thereby improving the gram capacity, first charge efficiency, peel strength, swelling performance, charge rate and cycle performance of the negative electrode sheet. In addition, the battery including the above-mentioned negative electrode sheet is also conducive to reducing the internal resistance (DCR).

[0051] Specific:

[0052] Embodiment 1:

[0053] This embodiment provides a method for preparing a high-capacity and high-rate negative electrode sheet, comprising the following steps:

[0054] Step 1: dissolving a silane coupling agent (KH550, γ-aminopropyltriethoxysilane) in an acidic solution to undergo a dicondensation reaction to obtain a mixed solution, wherein the acidic solution is a mixed solution of hydrochloric acid, ethanol and water, wherein the mass ratio of ethanol to water is 1:1, and the pH value of the acidic solution is 4. The pH value of the acidic solution can be adjusted by adjusting the content of hydrochloric acid. For example, 0.5 ml of 36% concentrated hydrochloric acid can be dissolved in ethanol and then constant volume can be obtained with a 500 ml volumetric flask to obtain an acidic solution with a pH value of 4, or it can be purchased from the market. The concentration of the silane coupling agent is 3 wt%, and the reaction time for obtaining the mixed solution is 40 min.

[0055] Step 2: Evenly mix the resin-based hard carbon material into the above-mentioned mixed solution, wherein the mass ratio of the hard carbon material to the silane coupling agent is 95:3. The hard carbon material is evenly mixed by stirring.

[0056] Step 3: Filter the mixed solution of step 2 to obtain a first mixture, and wash the first mixture with a large amount of deionized water until it is neutral.

[0057] Step 4: Add the conductive agent carbon black SP to the cleaned first mixture to obtain a second mixture, and add water to the second mixture to adjust the viscosity of the slurry to 3000-6000 mPa•s. The mass ratio of the hard carbon material, the silane coupling agent and the conductive agent is 95:3:2.

[0058] Step 5: Apply the above slurry to the current collector and dry it to obtain a pole roll. The slurry can be applied to one side of the current collector. The current collector is aluminum foil.

[0059] Step 6: Place the electrode coil in a vacuum oven and perform heat treatment under inert gas conditions at a temperature of 600°C for 2 hours. At the same time, a metal clamp is used to fix the electrode coil during the heat treatment process, and the clamping pressure provided by the metal clamp is 800 MPa. Thus, a negative electrode sheet that can be directly used is obtained.

[0060] Embodiment 2:

[0061] Different from Example 1, the silane coupling agent used in step 1 is KH570 (3-methylpropyltrimethoxysilane).

[0062] Embodiment 3:

[0063] The difference from Example 1 is that in step 1, the pH value of the acidic solution is 6.

[0064] Embodiment 4:

[0065] The difference from Example 1 is that in step 1, the reaction time for obtaining the mixed solution is 60 min.

[0066] Embodiment 5:

[0067] Different from Example 1, the mass ratio of the hard carbon material, the silane coupling agent and the conductive agent is 85:10:5.

[0068] Embodiment 6:

[0069] Different from Example 1, a biomass (coconut shell) based hard carbon material was selected.

[0070] Embodiment 7:

[0071] Different from Example 1, in step six, the temperature of the heat treatment is 800°C.

[0072] Embodiment 8:

[0073] The difference from Example 1 is that in step six, the heat treatment time is 1 hour.

[0074] Comparative Example 1:

[0075] Carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are used as binders, wherein the mass ratio of hard carbon (main material): SP (carbon black): CMC: SBR is 95:1.5:1.5:2.

[0076] Step 1: Gluing: CMC mixed with water, mass concentration 1.5%;

[0077] Step 2: Add the hard carbon main material step by step according to the above proportions;

[0078] Step 3: Add SP according to the proportion;

[0079] Step 4: Add water to adjust the viscosity, and control the viscosity at 3000-6000 mPa•s;

[0080] Step 5: Add SBR and mix evenly to obtain slurry with a viscosity of 2000-5000 mPa•s;

[0081] Step six: Coat the negative electrode slurry on the surface of the aluminum foil, roll-press, and vacuum dry at 110°C for 12 hours to obtain a negative electrode sheet.

[0082] Comparative Example 2:

[0083] Step 1: Dissolve the silane coupling agent (KH550) in a mixed solution of ethanol and water, wherein the pH of the mixed solution is 4, the concentration of the coupling agent is 3 wt%, and the mixing time is 40 min.

[0084] Step 2: Take a resin-based hard carbon material and add it to the above solution. The mass ratio of the hard carbon material to the coupling agent is 95:3. Stir until the slurry is uniform.

[0085] Step 3: Filter the above slurry and wash it with a large amount of deionized water until the mixture is neutral.

[0086] Step 4: Take the conductive agent SP and add it to the above mixture, and add water to adjust the viscosity of the slurry to 3000-6000 mPa•s, wherein the mass ratio of the hard carbon material, the coupling agent and the SP is 95:3:2.

[0087] Step 5: Coat the above slurry on the current collector and dry it.

[0088] A sodium ion battery is made by using sodium foil as the positive electrode, polypropylene as the separator, a liquid electrolyte (the specific preparation method is: mixing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7, and adding NaPF6 to form an electrolyte, and the concentration of NaPF6 is 1 mol / L), and the negative electrode sheet obtained in the above embodiments and comparative examples. The specific process can be referred to the existing preparation method, which will not be repeated here.

[0089] In addition, the reagents and additives used in the above-mentioned embodiments and comparative examples of the present application can all be purchased from the market and are all conventional reagents. Therefore, the purchase sources and corresponding brands are not described in detail.

[0090] The obtained sodium ion battery was subjected to a battery performance test, and the obtained negative electrode sheet was subjected to a mechanical strength test.

[0091] Specific test method:

[0092] (1) Gram capacity and first charge and discharge efficiency test: Place the sodium ion battery in a 25°C environment for 8 hours, discharge to 0V at 0.xC (x=1-3), discharge to 0V at 0.0xC (x=1-3); let stand for 5 minutes; charge to 2V at 0.xC (x=1-3). The charge capacity is taken as the final gram capacity value, and the ratio of the charge capacity to the discharge capacity is taken as the first charge and discharge efficiency value.

[0093] (2) Charging rate and cycle performance test: Place the sodium ion battery in an environment of 25°C, charge it to 4.0V at a constant current and voltage of xC (1C to 3C), set the cut-off current to 0.05C, and discharge it to 1.5V at a constant current of 0.7C. This charge and discharge step is recorded as one cycle. Repeat this cycle until the capacity retention rate is less than 80%, and record the number of cycles.

[0094] (3) Test method for peel strength:

[0095] The peel strength is measured by applying a certain force on the electrode to peel it off from the current collector. The test is performed using a universal tensile testing machine. Steps:

[0096] a Cutting pole piece

[0097] Take the rolled negative electrode sheet and use a customized die cutter to cut the electrode sheet, generally with a length of 400mm and a width of 10-50mm.

[0098] b. Paste and fix the pole piece

[0099] Take a flat thin steel plate, about 200-300mm long and 40-60mm wide; first stick a strip of double-sided tape on the center of the steel plate (the length should be greater than the sample test length and the same width as the electrode), smooth it with force to ensure that the double-sided tape is tightly attached to the center of the steel plate. Remove the double-sided tape and attach the electrode to the tape strip, making sure that the electrode and the tape are matched and attached.

[0100] cInstallation test

[0101] There are two upper and lower clamps on the tensile machine. Insert the steel plate with the fixed pole piece into the lower clamp and fix it vertically; insert the pole piece without glue into the upper clamp and fix it, so that the pole piece attached to the adhesive tape is 180° (or 90°) with the pole piece fixed by the upper clamp. After fixing the test sample, first calibrate and reset, set the test width, pole piece peeling length 50-150mm, peeling speed 50-100mm / min, and then start the test to get the peeling strength curve and average value.

[0102] (4) Specific test method for electrode swelling performance:

[0103] a. Cut a certain area of ​​electrode (usually) and put the dried electrode into the oven for drying. Then put the electrode into a watch glass and record the mass M1 together with the watch glass.

[0104] b At 60℃, soak the sample in a solution of excess EC (ethylene carbonate): EMC (ethyl methyl carbonate): DEC (diethyl carbonate) = 1:1:1 for 24 hours, drain the excess solution and record the mass M2.

[0105] c Calculate the liquid absorption rate (M2-M1) / M1

[0106] (5) Specific test method for battery internal resistance (DCR):

[0107] a Place the sodium ion battery in an environment of 25°C, charge it to 4.0V at a constant current and voltage of xC (1C to 3C), with a cut-off current of 0.05C, and record the battery capacity Q1 (100% SOC capacity); discharge it at a constant current of 0.7C until the cut-off value is 1 / 2Q1, and record the cut-off voltage V1;

[0108] b. Take any current from (1 to 10) C, usually 10 C current value I, discharge at a constant current for 10 seconds, and record the cut-off voltage V2 after stopping;

[0109] c Internal resistance (DCR) calculation = |V2-V1| / I.

[0110] The test results are shown in the following table:

[0111]

[0112] By comparing the test results of Examples 1 to 8 with Comparative Example 1, it can be seen that the negative electrode sheet provided by the present application has significant improvements in gram capacity, first charge efficiency, peel strength, swelling performance, charge rate, battery internal resistance (DCR) and cycle performance compared with the negative electrode sheet obtained by the existing binder treatment. By comparing the test results of Examples 1 to 8 with Comparative Example 2, it can be seen that the negative electrode sheet after high-temperature heat treatment has significant improvements in gram capacity, first charge efficiency, peel strength, swelling performance, charge rate, battery internal resistance (DCR) and cycle performance.

[0113] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a high-capacity and high-rate negative electrode sheet, characterized in that: include: Dissolving a silane coupling agent in an acidic solution to undergo a dicondensation reaction to obtain a mixed solution, wherein the silane coupling agent satisfies a chemical formula of YR-Si(OR)3, Y represents an organic functional group, R represents an alkyl group, the pH value of the acidic solution is 3-6, the concentration of the silane coupling agent in the mixed solution is 1 wt %-5 wt %, and the reaction time for obtaining the mixed solution is 30-60 min; At least uniformly mixing the hard carbon material into the mixed solution to obtain a slurry, wherein the mass ratio of the hard carbon material to the silane coupling agent is 80-97:2-15; Applying the slurry to a current collector and drying it to obtain a pole coil; The electrode coil is heat-treated under an inert atmosphere at a temperature of 500-900° C. for 1-2 hours to obtain a negative electrode sheet.

2. The method for preparing a high-capacity and high-rate negative electrode sheet according to claim 1, characterized in that: The preparation of the slurry also includes: filtering the mixed solution in which the hard carbon material is added to obtain a first mixture, and washing the first mixture with deionized water until it becomes neutral; adding a conductive agent to the first mixture after cleaning to obtain a second mixture; Add water to the second mixture and mix well to obtain the slurry.

3. The method for preparing a high-capacity and high-rate negative electrode sheet according to claim 2, characterized in that: The mass ratio of the hard carbon material, the silane coupling agent and the conductive agent is 80-97:2-15:1-5.

4. The method for preparing a high-capacity and high-rate negative electrode sheet according to claim 1, characterized in that: The viscosity of the slurry is 3000-6000 mPa•s.

5. The method for preparing a high-capacity and high-rate negative electrode sheet according to claim 1, characterized in that: When heat treating the pole coil, a metal clip is used to fix the pole coil.

6. A negative electrode sheet, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 5.

7. A battery comprising a positive electrode sheet and an electrolyte, characterized in that: It also includes the negative electrode sheet as claimed in claim 6, wherein the electrolyte is at least disposed between the positive electrode sheet and the negative electrode sheet.

8. The battery according to claim 7, characterized in that The battery further includes a separator, which is spaced between the positive electrode sheet and the negative electrode sheet, and the electrolyte is a liquid electrolyte.

Citation Information

Patent Citations

  • Battery electrode and method of manufacturing the same

    JP2011049046A